Absolute Knowing as a Problem - Tufano, Guiseppe (Pensamiento. Revista de Investigación e Información Filosófica, 2014)
This article analyzes absolute knowing as the Spirit’s last figure, introducing a double perspective (epistemological and logico-ontological) through which is finally possible the focusing on the Hegelian proposal in the Phenomenology. Furthermore, the article concentrates on the relationship between religious and absolute knowing from an epistemic and a structural point of view, aiming at an original understanding that is capable of restoring the conceptual horizon of the nascent speculative logic to which absolute knowing belongs.